Characterization of various cell lines from different ampullary cancer subtypes and cancer associated fibroblast-mediated responses. Issue 1 (December 2016) - Lai, Zon; Bolm, Louisa; Fuellgraf, Hannah; Biniossek, Martin; Makowiec, Frank; Hopt, Ulrich; Werner, Martin; Keck, Tobias; Bausch, Dirk; Sorio, Claudio; Scarpa, Aldo; Schilling, Oliver; et al.
Abstract Background Ampullary cancer is a relatively rare form of cancer and usually treated by pancreatoduodenectomy, followed by adjuvant therapy. The intestinal subtype is associated with markedly improved prognosis after resection. At present, only few cell lines are available for in vitro studies of ampullary cancer and they have not been collectively characterized. Methods We characterize five ampullary cancer cell lines by subtype maker expression, epithelial-mesenchymal transition (EMT) features, growth and invasion, drug sensitivity and response to cancer-associated fibroblast conditioned medium (CAF-CM). Results On the basis of EMT features, subtype marker expression, growth, invasion and drug sensitivity three types of cell lines could be distinguished: mesenchymal-like, pancreatobiliary-like and intestinal-like. Heterogeneous effects from the cell lines in response to CAF-CM, such as different growth rates, induction of EMT markers as well as suppression of intestinal differentiation markers were observed. In addition, proteomic analysis showed a clear difference in intestinal-like cell line from other cell lines. Conclusion Most of the available AMPAC cell lines seem to reflect a poorly differentiated pancreatobiliary or mesenchymal-like phenotype, which is consistent to their origin. We suggest that the most appropriate cell line model for intestinal-like AMPAC is the SNU869, while others seem to reflect aggressive AMPAC subtypes.